Health workers' leave frozen - The Sun (2009)
With the number of a(H1N1)cases climbing to 91 yesterday,and with the public getting worried over the rising numbers of local transmissions,the Health Ministry has decided to freeze leave for 100,000 of its staff nationwide untill further notice to ensure there is adequate manpower to contain the flu outbreak.